2022
DOI: 10.3389/fmicb.2022.965843
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic properties and biological activity of resuscitation-promoting factor B of Rhodococcus sp. (GX12401)

Abstract: Resuscitation-promoting factor B (RpfB) is one of the five members of Rpf-like family in Mycobacteriales, which have the resuscitation-promoting activity. Most strains of Rhodococcus also have RpfB gene, but the study of rpfB gene in Rhodococcus is not thorough. Here, we amplified the rpfB gene of intact Rhodococcus sp. (GX12401) and cloned it into pET30a (+) expression vector. Then a recombinant form of soluble RpfB was expressed in Escherichia coli BL21. The soluble recombinant RpfB was purified by Ni–Sephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The results showed that the recombinant Rpf-like protein from N. halophila had a significant resuscitation effect on the VBNC N. halophila , and the resuscitation effect was most obvious when 0.1 mg/mL of the recombinant Rpf protein was added ( Figure 5 and Figure 6 ), indicating that high concentrations of the Rpf protein inhibited the growth and recovery of VBNC N. halophila . This phenomenon is consistent with the results reported in the literature [ 53 ]. However, FDA and PI staining are not the best method because PI is not effective in distinguishing VBNC bacteria from bacterial death.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that the recombinant Rpf-like protein from N. halophila had a significant resuscitation effect on the VBNC N. halophila , and the resuscitation effect was most obvious when 0.1 mg/mL of the recombinant Rpf protein was added ( Figure 5 and Figure 6 ), indicating that high concentrations of the Rpf protein inhibited the growth and recovery of VBNC N. halophila . This phenomenon is consistent with the results reported in the literature [ 53 ]. However, FDA and PI staining are not the best method because PI is not effective in distinguishing VBNC bacteria from bacterial death.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, bacterial spore germination is a complex physiological process. Usually, Bacillus subtilis forms heat- and desiccation-resistant spores under conditions of nutrient limitation [ 53 ]. These dormant spores germinate when stimulated by various nutrient sources.…”
Section: Discussionmentioning
confidence: 99%